Kepribadian Introvert dan Kepribadian Ekstrovert Terhadap Minat Berwirausaha Mahasiswa Melalui Motivasi sebagai Variabel Mediasi - Dwi Kurniawan; Feny Tialonawarmi (IPM2KPE, 2023)
This study aims to determine and analyze the effect of introverted and extroverted personalities on student interest in entrepreneurship through motivation as a mediating variable. This research method is quantitative. Respondents in this study were undergraduate students at Jambi University. The data analysis method used in this study is the Partial Least Square (PLS) method using the Smart PLS application. The results showed that there was an influence of introverted personality on students' interest in entrepreneurship through motivation as a mediating variable and there was no effect of extroverted personality on students' interest in entrepreneurship through motivation as a mediating variable. Keywords: Extrovert Personality Introvert Personality, Interest in Entrepreneurship, Motivation